Further understanding of rolling contact fatigue in rolling element bearings - A review. (December 2019) - El Laithy, Mostafa; Wang, Ling; Harvey, Terry J.; Vierneusel, Bernd; Correns, Martin; Blass, Toni
Abstract: Rolling bearings are one of the most widely used components in industrial machinery. If suitably mounted, loaded, lubricated and isolated from contamination, rolling contact fatigue (RCF) is believed to be the most probable mode of failure resulting in subsurface originated failures. Over the past several decades many researchers have studied the failure and microstructural alterations in bearings such as dark etching regions and white etching bands and how operating conditions such as pressure, temperature and running time impact them during RCF. This paper aims to provide an overview of such alterations, their properties, formation mechanisms and impact on bearing failure.